Bimbingan Spiritual bagi Jamaah Santri Luwung - Arnis Rachmadhani (STAIN Bengkalis, 2016)
This qualitative research is about the phenomenon of contemporary religious life marked by the emergence of new religious movements. This religious phenomenon pared in three ways data collection techniques are observation, interview, and documentation which is analyzed with an interactive analysis model. Pasujudan Santri Luwung Padepokan Bumi Arum is growing rapidly in the regency of Sragen, the province of Central Java, when explored in depth, their teaching is kejawen meeting with Islam. This teaching as a new religious movement phenomenon, able to give a touch of social reality for member of Santri Luwung through spiritual guidance in a wide range of religious activities, namely in da>wah programs, social, educational, health, economics, and the arts.[Penelitian kualitatif ini membahas tentang fenomena kehidupan beragama kontemporer yang ditandai dengan munculnya gerakan agama baru atau lebih sering disebut sebagai new religious movements. Fenomena keagamaan ini dikupas melalui tiga cara teknik pengumpulan data yaitu teknik observasi, wawancara, dan dokumentasi yang kemudian dianalisa dengan model analisis interaktif. Pasujudan Santri Luwung Padepokan Bumi Arum yang ajarannya berkembang pesat di Kabupaten Sragen Provinsi Jawa Tengah, bila ditelaah secara mendalam, ajarannya merupakan pertemuan kejawen dengan Islam. Ajaran ini sebagai fenomena new religious movement, mampu memberikan sentuhan realitas sosial bagi jamaah Santri Luwung melalui bimbingan spiritual di berbagai macam aktifitas keagamaan, yaitu dalam program dakwah, sosial, pendidikan, kesehatan, ekonomi, dan kesenian.]